PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, BUDAYA ORGANISASI DAN LINGKUNGAN KERJA TERHADAP MOTIVASI KERJA PADA KARYAWAN CV. CIPTA LAYLA BINA KARYA (AYAM GEPREK LAYLA) - Alifah Febirika Nurjanah; Adi Santoso (STIE Trisna Negara OKU Timur, 2023)
This study aims to understand, describe, analyze and describe the influence of transformational leadership, organizational culture and work environment on work motivation in employees of CV. Cipta Layla Bina Karya (Chicken Geprek Layla). The research studied by researchers is a descriptive type with a quantitative approach. This study has a human resource population of all branches of 193 people. From the number of populations, it is possible to find the number of samples to be studied using the slovin formula. Where the number of samples found as many as 66 respondents. Sampling method taken accidental sampling. The coefficient of determination taken by the researcher is multiple linear regression analysis. The results of this study found that transformational leadership has no significant effect on work motivation. While organizational culture and work environment have a significant effect on work motivation of CV employees. Cipta Layla Bina Karya (Chicken Geprek Layla).